The Florida Department of Agriculture and Consumer Services (FDACS) Continuing Education Unit (CEU) System for Certified Pesticide Applicators - Frederick M. Fishel (EDIS, 2005)
This guide provides an update of the amended Continuing Education Unit system used by FDACS for recertifying pesticide applicators. This document is PI-40, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date April 2005.